2016
DOI: 10.3892/br.2016.712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factor VIII polymorphic short tandem repeat markers in linkage analysis for carrier diagnosis of hemophilia A

Abstract: Abstract. Hemophilia A (HA) is the most common inherited X-linked recessive bleeding disorder caused by heterogeneous mutations in the factor VIII gene (FVIII). Diagnosis of the carrier is critical for preventing the birth of children affected by this coagulation disorder, which ultimately facilitates its management. Due to the heterogeneous nature of mutations, the large inversions and the complexity of the FVIII gene, direct recognition of the disease-associated mutation in HA is complex. Indirect linkage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It is also difficult to develop this approach due to the large size of the F8 gene and the pathogenic variantal heterogeneity in HA. Therefore, we performed the linkage analysis of intragenic neutral variants of F8 gene for a rapid and economical carrier diagnosis strategy (Shrestha, Dong, Li, Huang, & Zheng, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is also difficult to develop this approach due to the large size of the F8 gene and the pathogenic variantal heterogeneity in HA. Therefore, we performed the linkage analysis of intragenic neutral variants of F8 gene for a rapid and economical carrier diagnosis strategy (Shrestha, Dong, Li, Huang, & Zheng, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that using STR markers can be very helpful in several ways for performing either PGDs 35 or in special cases of PNDs where hematological indices indicate that the parents are carrier/s of β-thal 36 , even when no mutation can be found using techniques like whole gene sequencing or MLPA 37 . In addition, haplotype analysis can be helpful when there is a time constraint to find the mutation and even confirming direct mutation analysis findings 38 .…”
Section: Discussionmentioning
confidence: 99%